Digital Fuzzy Current Controlled Light-Emitting Diode Driver with Power Factor Correction - Veerendra, A. S.; A. A., Shah; M., SubbaRao; Mohd Rusllim, Mohamed (Hindawi, 2021)
This paper presents the design and development of a fuzzy peak current controlled (FPCC) single-stage single-phase nonisolated AC/DC high-power factor LED drive. The proposed controller includes a fuzzy logic controller (FLC) in the loop voltage and a peak current controller in the loop current for an integrated nonisolated LED driver to attain a high-power factor (PF). The proposed control avoids complexities related to nonlinearities of the converter. The control action is initially derived from a group of rules written in accordance with experience and intuitive reasoning. The proposed technique is realized using a DSP processor (TI-TMS320F2812), which is capable of executing a high number of instructions in one cycle. A 70 W, 350 mA LED driver operating with an input of 90 V-230 V, 50 Hz was designed and implemented using MATLAB/Simulink. The results of the driver are in accordance with international regulations. The steady-state and transient responses are validated experimentally.